The generalized auto regressive conditional heteroskedasticity Parkinson range ( Garch-Park-R) model for forecasting financial volatility - Mapa, Claire Dennis S. (2004)
Abstract (A new variant of the ARCH class of models for forecasting the conditional variance, to be called the Generalized AutoRegressive model, is proposed. The GARCH-PARK-R model, utilizing the extreme values, is a good alternative to the Realized Volatility that requires a large amount of intra-daily data. The estimates of the GARCH-PARK-R model are derived using the Quasi-Maximum Likelihood Estimation (QMLE). The Parkinson Range is also used to evaluate the out-of-sample forecasting performance of 68 ARCH models using inter-daily data on the peso-dollar exchange rate. Finally, the variance of the conditional variance is estimated to generate the volatility of the volatility (VoV).
"March 2004."
Thesis (M.S. Statistics) --University of the Philippines, Diliman.
Keywords: Time series analysis; Econometrics; Foreign exchange rates -- Statistical methods